A REVIEW IN NANO CHEMISTRY AND DEVELOPING NEW MATERIALS TO COMBAT ENVIRONMENTAL POLLUTION - Asma Almabrouk Mousa; Mahmoud Abduesslam (Surman Journal of Science and Technology, 2024)
Nanochemistry is one of the most significant modern scientific fields, focusing on the synthesis and study of materials at the nanoscale, with dimensions ranging from 1 to 100 nanometers. This study highlights the importance of nanotechnology as a key tool in addressing urgent environmental challenges by enhancing the properties of materials used for pollution remediation. This is achieved by increasing the surface area of nanomaterials, leading to enhanced chemical and physical effectiveness. Nanoparticles also exhibit unique properties, such as higher biological activity compared to the same materials at larger scales (macroscale or microscale). These results come from a comprehensive study to provide a literature survey in the field of nanotechnology and its use in combating environmental pollution.